2016
DOI: 10.1007/s10103-016-1963-2
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effects of high-intensity laser therapy, manual therapy, and Kinesio taping in patients with subacromial impingement syndrome

Abstract: Subacromial impingement syndrome (SAIS) is a major contributing factor of shoulder pain; and treatment approaches (Kinesio® taping [KT], Exercise [EX], manual therapy [MT], and high-intensity laser therapy [HILT]) have been developed to treat the pain. The key objective of this study was to compare the effects of KT, MT, and HILT on the pain, the range of motion (ROM), and the functioning in patients with SAIS. Seventy patients with SAIS were randomly divided into four groups based on the treatment(s) each gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 39 publications
1
74
0
1
Order By: Relevance
“…25,26 Finally, 19 studies (HILT: 11, +other interventions: 8) were included for qualitative and quantitative assessment. [11][12][13][15][16][17]19,[31][32][33][34][35][36][37][38][39][40][41][42] The characteristics of all studies in two groups are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Finally, 19 studies (HILT: 11, +other interventions: 8) were included for qualitative and quantitative assessment. [11][12][13][15][16][17]19,[31][32][33][34][35][36][37][38][39][40][41][42] The characteristics of all studies in two groups are listed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…2,[6][7][8][9][10] Also, application techniques, the time of treatment and the cost of the device are different between these two generations of the laser therapy. [11][12][13] A recent systematic review indicated that HILT is effective in reducing musculoskeletal pain. 14 Adding therapeutic interventions to laser therapy is usual in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Kinesiotaping might serve as a method of management in shoulder impingement syndrome [1]. Kinesio taping was found to be effective on pain and function [2,3] kinesio taping seems to be better tolerated in the management of shoulder impingement and plays major role in conservative management [4,5]. Kinesio-Tape could provide a short-term alternative for patients with higher levels of kinesiophobia by decreasing fear and aiding in the patient's return to pre-injury levels of function and Kinesio-Tape may reduce pain in patients with musculoskeletal pain [6].…”
Section: Discussion On Hypothesesmentioning
confidence: 99%
“…it follows from the prepared literature review that tEns demonstrates poor evidence for effectiveness of pain relief in patients with fibromyalgia and is much less effective than electroanalgesia in the form of electro-acupuncture (Ea) or percutaneous electrical nerve stimulation (pEns) [87]. as regards laser light therapy, what has been indicated has been a higher effectiveness in elimination of pain through the use of Hilt in comparison with lllt in the treatment of rotator cuff pain (pain and disability minimization, improvement of movement range) [87,88] and in muscle and fascia pain of the trapezius dorsi muscle [89]. a short-term painkilling effect using Hilt was confirmed in patients treated for subacromial conflict, frozen shoulder or inflammation of the lateral epicondyle of the humerus.…”
Section: C) Palpitation Examinationmentioning
confidence: 99%